Recognition of prior learning candidates' experiences in a nurse training programme - Nomathemba B. Mothokoa; Jeanette Maritz (AOSIS, 2018)
Recognition of prior learning (RPL) in South Africa is critical to the development of an equitable education and training system. Historically, nursing has been known as one of the professions that provides access to the training and education of marginalised groups who have minimal access to formal education. The advent of implementing RPL in nursing has, however, not been without challenges. The purpose of this study was to explore and describe the experiences of RPL nursing candidates related to a 4-year comprehensive nursing training programme at a nursing education institution in Gauteng. An exploratory, descriptive and contextual qualitative research design was undertaken. The research sample comprised 13 purposefully selected participants. Face-to-face individual interviews, using open-ended questions, were used to collect data, which were analysed using Tesch's approach. Recognition of prior learning candidates experienced a number of realities as adult learners. On a positive note, their prior knowledge and experience supported them in their learning endeavours. Participants, however, experienced a number of challenges on personal, interpersonal and socialisation, and educational levels. It is important that opportunities are created to support and assist RPL candidates to complete their nursing training. This support structure, among others, should include the provision of RPL-related information, giving appropriate advice, coaching and mentoring, effective administration services, integrated curriculum design, and a variety of formative and summative assessment practices.